Role of regulatory pathways and multi-omics approaches for carbon capture and mitigation in cyanobacteria. (December 2022) - Kumar, Niwas; Kar, Srabani; Shukla, Pratyoosh
Graphical abstract: Highlights: Cyanobacteria are photosynthetic chassis for effective CO2 sequestration. Their metabolic flexibility enables them to utilize multiple carbon sources. Various aspects of regulatory pathways for CO2 mitigation are discussed. Cyanobacteria provide dual benefit of carbon sequestration and sustainable products. Abstract: Cyanobacteria are known for their metabolic potential and carbon capture and sequestration capabilities. These cyanobacteria are not only an effective source for carbon minimization and resource mobilization into value-added products for biotechnological gains. The present review focuses on the detailed description of carbon capture mechanisms exerted by the various cyanobacterial strains, the role of important regulatory pathways, and their subsequent genes responsible for such mechanisms. Moreover, this review will also describe effectual mechanisms of central carbon metabolism like isoprene synthesis, ethylene production, MEP pathway, and the role of Glyoxylate shunt in the carbon sequestration mechanisms. This review also describes some interesting facets of using carbon assimilation mechanisms for valuable bio-products. The role of regulatory pathways and multi-omics approaches in cyanobacteria will not only be crucial towards improving carbon utilization but also will give new insights into utilizing cyanobacterial bioresource for carbon neutrality.